2019
DOI: 10.3390/polym11081269
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Swelling Properties of Smart Multiresponsive Core-Shell Microgels by Copolymerization

Abstract: The present study focuses on the development of multiresponsive core-shell microgels and the manipulation of their swelling properties by copolymerization of different acrylamides—especially N-isopropylacrylamide (NIPAM), N-isopropylmethacrylamide (NIPMAM), and NNPAM—and acrylic acid. We use atomic force microscopy for the dry-state characterization of the microgel particles and photon correlation spectroscopy to investigate the swelling behavior at neutral (pH 7) and acidic (pH 4) conditions. A transition bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 53 publications
(68 reference statements)
0
8
0
Order By: Relevance
“…The effect of α-methyl substitution on the interpolymer complex showed that α methylation provides higher glass transition temperatures (168-228 • C) and delays of thermal degradation [22]. The structure of doubly-temperature sensitive core-shell microgels based on p(NiPMAm) and p(NiPAm) was examined [23,24]. The swelling and mechanical behavior of negatively charged p(NiPMAm) hydrogels, depending on temperature in water and in aqueous NaCl solutions at room temperature, were investigated [25].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of α-methyl substitution on the interpolymer complex showed that α methylation provides higher glass transition temperatures (168-228 • C) and delays of thermal degradation [22]. The structure of doubly-temperature sensitive core-shell microgels based on p(NiPMAm) and p(NiPAm) was examined [23,24]. The swelling and mechanical behavior of negatively charged p(NiPMAm) hydrogels, depending on temperature in water and in aqueous NaCl solutions at room temperature, were investigated [25].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent addition of a reducing agent confined metal nanoparticles within their gel templates. This incorporation method offers the advantage that the nanoparticles can be specifically incorporated at the particular copolymer localization, [32,65,66] instead of randomly dispersing them throughout the microgel material. [67] In our study we wanted to incorporate an equal amount of palladium surface per polymer mass in the microgels so that the respective palladium surfaces are surrounded with different MAc concentrations in the microgel network.…”
Section: Nanoparticle Characterizationmentioning
confidence: 99%
“…By switching between charged and uncharged states depending on the solution pH, these monomers govern the microgel's swelling by promoting electrostatic repulsion among the chains and forming hydrogen bonds with water. [142][143][144][145] For example, Li et al sandwiched AA-containing microgels between thin films and utilized the pH-induced microgel swelling to vary the distance between the films. [33] Giraud et al explored the effects of charge and inter-particle spacing on the sliding friction between sheets of pH-responsive P(S-co-AA) microgels.…”
Section: Ph-responsive Monomersmentioning
confidence: 99%